EVALUATION OF ACACIA GERRARDII BENTH. (FABACEAE: MIMOSOIDEAE) AS A HONEY PLANT UNDER EXTREMELY HOT-DRY CONDITIONS: FLOWERING PHENOLOGY, NECTAR YIELD AND HONEY POTENTIALITY - Abdulaziz Saad Alqarni; Awad Mohamed Awad; Ayman Ahmad Owayss (Journal of Animal and Plant Sciences, 2015)
The nature of both bee-plant interactions and pollination ecology critically depends on flowering phenology and nectar yield. These two factors determine whether the plant has the potential to produce honey by honey bees. Here, we characterized flowering phenology, quantified nectar yield and calculated honey potentiality of Talh (Acacia gerrardii Benth.). Talh is a widespread melliferous species distributed in Africa and the Middle East. Field investigations were performed in Rawdhat-Khoraim oasis, Riyadh, Saudi Arabia, from April to August for 3 years (2011-2013). Flowering phenology, nectar yield and tree canopy area data were used to predict the honey production potential of Talh trees. The bloom season of Talh trees began around mid-May and ended in mid-August. Flower density varied significantly (p˂0.001) among months, while the general mean (±SE) was 148±14 flower heads (FHs) per m2 per day. The total soluble solids (TSS) secreted were 30.4 mg/ FH/ day. Talh trees may produce potential honey weighing 495 ± 60 g/ tree/ day and 45,032 ± 6,359 g/ tree/ season. In conclusion, Talh trees have a high potential for honey production. Further studies are needed to estimate the actual honey production and to understand other aspects of flowering.
Keywords: Apis mellifera; Acacia gerrardii; flowering; honey; honeybees; nectar; pollination; Saudi Arabia